Prevention of vault prolapse in cases of procedentia using combined vaginal and laparoscopic approach for vault suspension: Agrawal’s technique - Agrawal, Priti; Agrawal, Rishi; Chandrakar, Jyotirmay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The objective of the current study was to assess the need of vault suspension after completion of hysterectomy in all cases of procedentia to prevent vault prolapse and to reduce the operating time for sacrocolpopexy using combined vaginal and laparoscopic approach by two surgeons. Methods: A total of 25 women undergoing surgery for procedentia were included. After completion of hysterectomy the need for vault suspension was assessed intraoperatively. In all cases polypropelene mesh was fixed vaginally to the uterosacral and cardinal ligaments. Vaginal vault was closed vaginally. Laparoscopic surgeon did laparoscopic sacrocolpopexy (LSC). Intraoperative and post-operative complications were then evaluated. Results: Our average operating time was 35 minutes for vaginal hysterectomy and 15 minutes for LSC. The shorter duration of surgery was because mesh was fixed vaginally and trackers were used to fix the mesh to sacral promontory. Intraoperative complications like bladder, ureteric, bowel injuries and hemorrhage were nil in our series. Postoperative stay in hospital was uneventful and all cases were discharged on second postoperative day. Conversion rate to laparotomy was nil. All cases have completed follow up for 5 years with 100% subjective and objective improvement. Conclusions: Restoration of vagina to its normal anatomic position remains the most important fact to prevent vault prolapse. Our technique is very easy, less time taking with negligible complication rates.